2022
DOI: 10.1007/s00125-022-05839-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in NOD mice reveals that B cells are highly educated by the pancreatic environment during autoimmune diabetes

Abstract: Aims/hypothesis B cells play an important role in driving the development of type 1 diabetes; however, it remains unclear how they contribute to local beta cell destruction during disease progression. Here, we use gene expression profiling of B cell subsets identified in inflamed pancreatic tissue to explore their primary functional role during the progression of autoimmune diabetes. Methods Transcriptional profiling was performed on FACS-sorted B cell sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Increasing evidence supports the notion that B cell development, differentiation, function, and metabolism have significant impacts on the development of T1D ( 86 89 ). Nonobese diabetic (NOD) mice serve as an exceptional model for investigating type 1 diabetes in human ( 90 ). Studies have shown that NOD mice with B cell defects are protected from T1D development ( 91 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Increasing evidence supports the notion that B cell development, differentiation, function, and metabolism have significant impacts on the development of T1D ( 86 89 ). Nonobese diabetic (NOD) mice serve as an exceptional model for investigating type 1 diabetes in human ( 90 ). Studies have shown that NOD mice with B cell defects are protected from T1D development ( 91 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%